Lydgate and the lenvoy - Nuttall, J (Taylor and Francis, 2018)
This article charts the development of the lenvoy (or envoy) in English courtly verse in the fifteenth century, looking in particular at the poetry of Hoccleve and Lydgate. It first offers a brief account of the lenvoy’s formation. Then, drawing on recent theorizations of poetry’s self–authorizing form, it argues that these authors use changed, elaborated or upgraded form to emphasize poetry’s ability to legitimate itself. It explores the role this legitimating form plays in establishing the relationship of poet and poem to patron and audience. In Lydgate’s Fall of Princes, the lenvoy moves from a work’s periphery to become a key structural element of this advice text. A concluding section traces the lenvoy’s influence as a site for self–theorization on later Lancastrian and early Tudor authors